(untitled) (Journal of the College of Basic Education, 2024)
In this research, we identified the impact of the Schwartz model on developing reading comprehension among fifth-grade primary school students at Yanbu’ al-Iraq School. 86 male and female students are selected from them and divided into two groups of 43 students each. After verifying their equivalence, a skills questionnaire consisting of 45 statements was constructed to measure direct, inferential, and critical understanding skills. Its stability and validity are verified, and after testing procedures to measure the effect of applying the Schwartz model on students, the following was revealed: Employing the Schwartz model affects students’ reading comprehension, and it is shown through the Eta squared coefficient that the overall effect size is large. Employing the Schwartz model affects students’ deductive understanding more than direct and critical understanding. There are no differences between females and males after applying the Schwartz model in students’ reading comprehension